LB3 Asepsis and monitoring during us guided peripheral regional anesthesia blocks. (11th August 2022) - Arslan, M; Srinivasan, K; Conroy, P; Mahmood, K
Abstract : Background and Aims: Ultrasound(US) guided techniques have been preferably used for peripheral nerve blocks. However, to follow aspetic measures for these procedures is still challenging. The purpose of this re audit is to know the best compliance of the doctors to the asepsis protocols defined on the basis of quality improvement audit done in September 2021 for peripheral nerve blocks using US machine. Methods: This was an observational study done in a tertiary Hospital of Dublin in one month duration. A questionnaire was handed to the anesthetic nurses and data was collected with respect to the type of block performed, aseptic techniques employed and the use of monitoring. Results: A total of 42 blocks were included in this study; single shot (100%), lower limb blocks (88%) were in majority. Aseptic techniques outlined by the Association of Anesthetists of Great Britain and Ireland were followed 100%inall cases including use of sterile gloves, drapes, skin decontamination, hand washing and the use of sterile gel and probe cover, except the use of sterile gown(20%). In comparison to the last audit in 2017, the percentages were as follows: Use of sterile gloves (93%), drapes (85%), skin decontamination (93%), sterile gowns(0%)and sterile probe cover(91%). Interestingly, Level 2 monitoring was done by 100% block performers both times. Conclusions: In comparison to previous audit, asepsis protocols except for sterile gowns were strictly followed by all the block performers and it has markedly reduced the chances of cross contamination.